Pengaruh Musik Dalam Mengembangkan Kreativitas Pada Mata Kuliah Pembelajaran Seni Rupa di IAIN Ponorogo - Tirta Dimas Wahyu Negara; Angga Fitriyono (Universitas Negeri Surabaya, 2022)
Music is a feeling that can be heard through rhythm, melody, timbre with its own harmony in each chant. Music is often used as a stimulant to arouse the emotional aspects of a person. Therefore music can also help the body and mind to work together in doing a job. Students at IAIN Ponorogo in the Fine Arts Learning course will get musical stimulants with different genres to be able to feel the impact and difference. The aim is to find out the extent of the impact given by music in an effort to provide comfort in the classroom. The types of music chosen are pop, rock and instrumental genres. This study uses a mixed method in the form of a combination of methods (quantitative and qualitative). The quantitative method functions as an explanatory with technical data analysis using simple linear regression using IBM SPSS V 24 software, while data were collected through interviews and questionnaires. The results of this study are 1) Music has a significant impact when creating art, 2) Music genres that suit taste can add to the mood in activities, 3) Inner calm affects the discovery of creative ideas. Based on these results, it can be concluded that music has a significant influence on someone to be able to find comfort in creating art.